Factors That Hinders Student’s Motivation – A Case Study Of Albania - Lila, Bukurie (European Scientific Journal, ESJ, 2016)
Not everyone can invent theories to change the world forever. However, everyone can use motivation to achieve personal success beginning from a young age. One of the most difficult and most important aspect of a teacher’s work is the student’s motivation. Students who are not motivated cannot learn effectively. They fail to take the information provided, and are not willing to participate in the lessons. Also, some of them may become problematic in the course of the learning process. The aim of this study is to show the role teachers should play with regards to the students, the methods that he should use, and the techniques and teaching strategies that teachers should use in the classroom so that students will be motivated. The study is focused on the high school classes. Thus, they are also the most problematic category to focus on learning if there are no good techniques to motivate them. The methodology followed in this work is qualitative and quantitative. We interviewed 15 high school teachers in Tirana Economic Technical School and had a survey of about 80 students of this school, classes 10, 11, and 12. The purpose of the theme is to identify the gaps that exist in the motivation of the students in the classroom. This study provides recommendations on how to use the process of motivation to meet the individual needs of each student and to increase their productivity. Therefore, this will result to a future generation of people who are eager to go to school.